Lope de Vega, poeta del Santísimo Sacramento - López Martínez, José Enrique (My University, 2017)
In this work I survey all information concerning Lope de Vegaʼs participation in both congregations of Slaves of the Blessed Sacrament founded in Madrid in 1608, after some news were spread of alleged vexations to the Sacrament of the Altar in England. At the same time, I provide an inventory of all of Lopeʼs poems devoted to the Eucharist, and of those conceivably produced for activities of both congregations, studying the circumstances of writing when possible. In this analysis, the political aspect that this particular devotion had for the author is highlighted through its poetic expression (specially in the context of the conflicts between Spain and England): from some poems presented to competitions at the end of the 16th Century and beginning of the 17th, to the major poems of his older years, mainly the Triunfos divinos and the Corona trágica., En este trabajo se revisan todas las noticias sobre la participación de Lope de Vega en las dos congregaciones de Esclavos del Santísimo Sacramento que se fundaron en Madrid, después de la difusión de noticias sobre presuntos agravios al Sacramento del Altar en Inglaterra en el año de 1608. Al mismo tiempo, se hace un inventario de todas las poesías del Fénix dedicadas al tema de la Eucaristía, y de las producidas posiblemente en actividades de las congregaciones, estudiando en varios casos sus circunstancias de escritura. En este análisis, se pone de relieve el aspecto político que esta devoción particular tuvo para el autor (especialmente en relación con los conflictos que enfrentaron a España e Inglaterra) a través de su expresión poética: desde algunas poesías presentadas en justas poéticas a fines del siglo XVI y principios del XVII hasta los poemas mayores de su etapa de madurez, principalmente los Triunfos divinos y la Corona trágica.
Keywords: Lope de Vega; Congregation of Slaves of the Blessed Sacrament, Madrid; Religious Poetry; Eucharist; Lope de Vega; Congregación de Esclavos del Santísimo Sacramento, Madrid; Poesía religiosa; Eucaristía